Cover Feature: Assembly of Sub‐Crystals on the Macroscale and Construction of Composite Building Units on the Microscale for SAPO‐34 (Chem. Asian J. 20/2018). Issue 20 (1st October 2018) - Yuan, Delin; Xing, Aihua; Miao, Ping; Sun, Qi; Cui, Lishan; Wang, Hui; Ma, Linge; Chiang, FuKuo; Kong, Jiechen
Abstract : The mechanistic study of molecular sieves from amorphous species to shaped crystals is one of the most difficult topics and is not yet completely understood. In this study, one plausible formation pathway has been proposed based on the evolution of SAPO‐34 crystals in a crystallization process using triethylamine (Et3 N). It was found that sub‐crystals with pyramidal structure can be formed in the initial synthesis stage and assemble to whole cubic crystals according to a proper arrangement. More information can be found in the Full Paper by Aihua Xing, Qi Sun et al. onpage 3063 in Issue 20, 2018 (DOI:10.1002/asia.201801069 ).